The effectiveness of coconut water in inhibiting shigella sp. bacteria from diarrhea - Mujahid, Ikhsan; Mulyanto, Arif; Khasanah, Tyas Ulfah (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2019)
Background: Diarrhea is still a serious problem for some people. It can be affected by the Shigella sp. bacteria. Some villagers drink tender coconut water (Co-cos nucifera L) to cure diarrhea. Some types of consumed tender or green coconut are green coconut, brown coconut, wulung green coconut, and wulung brown coconut. It is necessary to determine the contribution of coconut types to treat diarrhea caused by the Shigella sp bacterium. Objective: to determine the benefit of several types of coconut water toward diarrhea caused by bacteria such as Shigella sp. Method: The method implemented was to determine the benefit of tender coconut water toward Shigella sp bacteria was experimental study through Kirby-Bauer test (antibiotic disc). The study selected water of green coconut, brown coconut, wulung green coconut, and wulung brown coconut, while the positive control used Lodia diarrhea drug and negative control used aquadest (Purified water). Testing data of green coconut water toward Shigella sp. was analyzed through analysis of variance (ANOVA) with F test at 95% significant level. Then it was continued by Duncan test at 95% significant level. Results: The results of testing some green coconut water, positive control and negative control on Shigella sp bacteria can be seen from the clear zone formed around the antibiotic disc, green coconut showed 6.63 mm, brown coconut was 6.57 mm, wulung green coconut was 16.63 mm, wulung brown coconut was 9.23 mm, lodia diarrhea drug was 12.33 mm and purified water was 7.27 mm. Conclusion: all green coconut water is able to inhibit the growth of Shigella sp. The best inhibitor is obtained from the administration of wulung green coconut water with 16.6 mm diameter of the inhibition zone